2009
DOI: 10.1111/j.1365-2109.2008.02140.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection of probiotic bacteria for use in shrimp larviculture

Abstract: Three candidate probiotics, Bacillus foraminis, Bacillus cereus biovar toyoi and Bacillus fusiformis, were isolated from hydrogen-producing fermented solution and identi¢ed using 16S rRNA sequence analysis. Bacillus foraminis and B. cereus biovar toyoi exhibited strong antagonism against Streptococcus iniae and Photobacterium damselae subsp. piscicida in in vitro co-culture for competitive exclusion assay and then were conducted in the larviculture system of Penaeus monodon reared from zoea 1 to postlarva 1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 41 publications
4
31
0
2
Order By: Relevance
“…Treatment Mix-2 increased survival and larval development, compared to the control group. Similar results were found by Guo et al (2009), where B. fusiformis increased survival and accelerated metamorphosis of P. monodon and L. vannamei larvae. This study demonstrated that management that combines properly selected Bacillus isolates are a good option in larviculture to improve health, rate of development, and rate of survival of whiteleg shrimp.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Treatment Mix-2 increased survival and larval development, compared to the control group. Similar results were found by Guo et al (2009), where B. fusiformis increased survival and accelerated metamorphosis of P. monodon and L. vannamei larvae. This study demonstrated that management that combines properly selected Bacillus isolates are a good option in larviculture to improve health, rate of development, and rate of survival of whiteleg shrimp.…”
Section: Resultssupporting
confidence: 85%
“…In our study, Bacillus tequilensis (strain YC5-2), B. endophyticus (strains C2-2 and YC3-b), and B. amyloliquefaciens (strain YC2-a) significantly increased development of larvae (Luis-Villaseñor et al, 2011). Using probiotics, modification of bacterial communities in tank water improves cultivation of larval crustaceans (Balcazar et al,2007b;Garriques and Arevalo, 1995;Gómez et al, 2008;Guo et al, 2009;Nogami and Maeda, 1992) and bivalves Langdon (1993, 1994); Riquelme et al, 1996Riquelme et al, , 1997Riquelme et al, , 2001). Our study advances previous work demonstrating that probiotics maintain a balanced and natural bacterial community that improves production of shrimp larvae, which is also reflected in the rate of development, as demonstrated in our two bioassays with Bacillus spp.…”
Section: Larval Culturementioning
confidence: 55%
“…Although, the treatments with the probiotic showed higher survival rates than the control groups without probiotic. These results confirm those found by Guo et al (2009) for larvae of Pennaeus monodon fed with the probiotic Bacillus fusiformis; they found no significant difference in the survival rate when compared to the control group (without probiotic).…”
Section: Survival and Weight Gainsupporting
confidence: 82%
“…This stage normally involves the isolation of dozens or even hundreds of strains. Following isolation, several in vitro selection tests are usually performed, such as pathogen inhibition (Guo et al, 2009), production of digestive enzymes (Ochoa-Solano, 2006), production of antimicrobial substances (Vázquez et al, 2005;Sugita et al, 2007), growth rate (Vine et al, 2004a), and ability to adhere to the intestinal epithelium (Vine et al, 2004b), in order to select certain strains for in vivo assays.…”
Section: Introductionmentioning
confidence: 99%